Tegami Bachi, Letter Bee. Volume 4, A letter full of lies - Asada, Hiroyuki, 1968- (Viz Media, 2011)
"Lag, now a Letter Bee rookie, meets Dr. Thunderland, Jr., a peculiar man who collects and catalogs the various Amberground species. When the doctor takes a particular interest in Steak, Lag and Niche have to hustle to keep him off the doctor's dissection table! The ensuing chaos pays off for Lag when the doctor reveals that Gauche, Lag's missing hero, paid the doctor a visit before he disappeared."--Cover.